Users behaviors: The Heritage of Digital World - Danesh Moghadam, Atefeh; Alagha, Alireza (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In the advent of information era, not only digital world is going to expand its territories, it is going to penetrate into the traditional notions about the meaning of the words and also valorize new concepts. According to Oxford Dictionary, the word heritage is defined: The history, tradition and qualities that a country or society has had for many years and that are considered an important part of its character. In order to present how emerging patterns, as the consequences of technology development, are going to be considered as the new concept of heritage, we follow four steps. In the first step, we present the convergence of Information, Communication and Technology (ICT) and a concise history of its convergence. In the second step, we argue how convergence has culminated in emerging patterns and also has made changes in digital world. In the third step, the importance of users behaviors and its mining is surveyed. Finally, in the fourth step; we illustrate User Generated Contents (UGC) as the most prominent users behaviors in digital world.